The dynamics of an emerging outcomes-based educational approach in a second language English classroom - Westphal, Vivian (Rhodes University, Faculty of Education, Department of Education, 2000)
Curriculum 2005 and outcomes-based education was introduced to South African educators in 1996 by the Minister of Education, Prof. S.M.E. Bengu as an alternative to the racially divided education system prior to the first democratic elections of 1995. The new curriculum was designed to transform the education system into a more equitable system by focussing on creating learners who would become creative thinkers, independent, productive workers and responsible, non-racial citizens. Learners would take a greater role in their own education and teachers would take on new roles as facilitators in the learning process. The new approach was introduced into grade 1 in 1998 and grade 2 in 1999. By using a modified ethnographic approach, this research project studies how one teacher has begun to think about Curriculum 2005 and implement an OBE approach to ESL teaching in a grade 2 classroom. It also focuses on gaining insights into how the teacher has attempted to make sense of the new curriculum in terms of her current practice and the training she has received in OBE. The ethnographic approach of the thesis has allowed the researcher to draw on many forms of data providing a holistic view. Tentative findings show that the teacher is experiencing difficulty in "unpacking" the underlying principles of OBE in terms of her current methods of teaching ESL. She continues to work from tacit knowledge. Because she has received very little training in OBE, she lacks the tools to become a more reflective practitioner. Despite this, her ESL lessons show a positive communicative approach to language teaching by focusing on stories, rhymes and songs as comprehensible input for the learners. The findings of this thesis tentatively suggest that unless teachers are given more adequate training and learning support materials, their classroom practices will remain relatively unchanged.
Keywords: English language -- Study and teaching -- Foreign speakers -- South Africa; Competency-based education -- South Africa